Régionalisme et modernisme au Brésil : dialogues entre fléaux anciens et localismes modernes - André Tessaro Pelinser (Caravelle)
Investigating some works of Brazilian Romanticism, designated as “pre-Modernist” Regionalism and Modernism, this paper dwells upon the parties concerned by the intellectual debates from the turning of the 19th century to the beginning of the 20th, aiming to prove how part of the arguments used either by artists or critics obliterated relevant gaps in order to understand the tensions which arose from the modernization processes in progress. We discuss, then, how Brazilian literature produced modern art before reaching Modernism, conscious that this fact is frequently ignored.